PENGARUH ASIMETRI INFORMASI TERHADAP MANAJEMEN LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Andrie Mustikawati; Nur Cahyonowati (Diponegoro Journal of Accounting, 2015)
Thestudy aimed to analyze the effect of information asymmetry on earnings management by considering managerial ownership as moderating variables. This study uses variable earnings management as a dependent, the dependent variable is measured by using a proxy for discretionary accruals. Information asymmetry used as independent variables, information asymmetry is measured by a proxy bid-ask spread. This study also uses moderating variable is firm size, firm size is measured by the proxy of the total assets of the company.In this study using the manufacturing companies listed in Indonesia Stock Exchange (IDX) and the Indonesian Capital Market Directory (ICMD) in 2012-2013 as the sample. The sample was selected using purposive sampling. The analysis technique used is Moderated Regression Analysis.The results of the analysis explains that the asymmetry of information has a significant impact on earnings management in a positive direction. While the size of the company may moderate the effect of information asymmetry on earnings management.